Family history of autoimmune diseases is associated with an increased risk of autism in children: A systematic review and meta-analysis. (August 2015) - Wu, Shunquan; Ding, Yingying; Wu, Fuquan; Li, Ruisheng; Xie, Guoming; Hou, Jun; Mao, Panyong
Highlights: We summarized the association between autoimmune diseases (ADs) and autism risk. A higher risk of autism in children with family history of ADs was identified. Consistent results were obtained for all ADs combined and some specific ADs. More mechanistic studies are needed to make further explanation. The trigger and mechanism for the underlying pathology in autism is still unknown. Abstract: Background: We conducted a systematic review and meta-analysis to summarize the current evidence on the relationship between family history of autoimmune diseases (ADs) and risk of autism in children, as current evidence suggests inconsistent results. Methods: We identified relevant studies by searching PubMed, EmBase, and Web of Science databases up to Dec 2014. Risk estimates from individual studies were pooled using random-effects models. Sub-groups analyses were conducted by some study-level factors. Publication bias was assessed by funnel plots, Egger's regression test and Begg–Mazumdar test. Results: A total of 11 articles were included in the meta-analysis, including 3 cohort studies, 6 case-control studies, and 2 cross-sectional studies. The meta-analysis showed that family history of all ADs combined was associated with a 28% (95% CI: 12–48%) higher risk of autism in children. For some specific ADs, evidence synthesis for risk of autism in children showed a statistically significant association with family history of hypothyroidism (OR = 1.64, 95% CI: 1.07–2.50), type 1 diabetes (OR = 1.49, 95% CI: 1.23–1.81), rheumatoid arthritis (OR = 1.51, 95% CI: 1.19–1.91), and psoriasis (OR = 1.59, 95% CI: 1.28–1.97). The results varied in some subgroups. Conclusion: An overall increased risk of autism in children with family history of ADs was identified. More mechanistic studies are needed to further explain the association between family history of ADs and increased risk of autism in children.